Motorcycles Retirement Program: Choosing the Appropriate Regulatory Framework - Tomohara, Akinori; Xue, Jian (2012)
This paper studies instrument choice under market-based regulations when governments expropriate private property in order to protect the environment. The analysis uses survey data collected for Bangkok's old motorcycle retirement program. While the literature studies only "Cash for Clunkers" schemes, this hypothetical experiment allows us to compare owners' preferences for alternative schemes. Policy implications of the proposed schemes can be inferred after examining owners' responses to different financial incentive provided by the government. Our analysis provides criteria that could be used when choosing one scheme over another.